Institutional issue proclivity in the EU: the European Council vs the Commission. Issue 5 (14th May 2017) - Alexandrova, Petya
ABSTRACT: Macropolitical institutional venues deal with a large scope of policy areas but, due to cognitive and institutional constraints, process information serially. Therefore, they can be expected to demonstrate issue proclivity – long-term specialization in a narrow set of topics. In the European Union (EU), the European Council and the Commission form a dual executive. Their distinctively different functional roles imply differences in institutional issue proclivity, which are empirically tested on 12 years of output agendas data. The European Council exhibits issue proclivity towards soft law domains, whereas the Commission towards exclusive EU competencies, the common market and flanking regulatory affairs. The European Council's remit is rather protected but the Commission is more vulnerable. As the fields of business and energy demonstrate, the European Council can temporally become more active in Commission proclivity domains in the context of large-scale crises and political salience of big projects.